Study Pemanfaatan Abu Bonggol Jagung Sebagai Bahan Substitusi Semen Untuk Beton Normal - Maria Prisila Hederanti Itu; Herman Parung; Junus Mara (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
Advances in construction fields resulting in increase in material prices such as cement so that study is carried out to improve concrete quality using materials that are easy to obtain as well as environmentally friendly. One of them is corn cob ash that is known to contain successive that can tie the aggregate of the concrete mixture. This study aimed to know the composition of concrete mixture with the use of corn cob ash and the effect on concrete characteristics in the variety 0%, 5%, 10%, and 15%. This study uses method mix design is American Concrete Institue (ACI) with planned concrete quality f’c 30 MPa and uses a cylinder dimensional 15 × 30 cm and beam dimension 60 × 15 × 15 cm. The result showed that corn cob ash can’t increase concrete characteristics in the variety above 4%.